The Essence of Critical Literacy in The Learning Process in Indonesian Higher Education - Ahmad Arkam Ramadhani; Abdul Rahman R; Chaerul Fadlan Saud (Phonologie : Journal of Language and Literature, 2025)
Abstract. This study examines how three English professors at Universitas Muhammadiyah Bulukumba in Indonesia apply critical literacy techniques in an EFL classroom. Understanding how these lecturers incorporate critical literacy into their lessons and identifying the difficulties they face are the goals of the study. A thorough understanding of the methods and experiences of 90 students and three lecturers was obtained through interviews and classroom observations. According to the results, the lecturers successfully implemented the five-step instructional framework of critical literacy, which entails encouraging students to read and think critically outside of the text, engaging them in inquiry, and fostering group discussions. The lecturers were able to successfully combine critical literacy techniques with conventional teaching approaches, even though they relied on textbook resources. By asking important questions and encouraging group conversations, they established a space where students felt free to voice their thoughts. In addition to improving pupils' critical thinking abilities, this method encouraged social awareness, tolerance, and accountability. Nevertheless, the study also identifies a number of difficulties in putting critical literacy practices into practice. The main obstacle was the pupils' poor language skills, which prevented them from fully interacting with the materials and debates. A lack of knowledge of critical literacy principles and ingrained teaching approaches also made it challenging to change classroom procedures to include critical literacy. The lecturers also had to deal with limitations relating to insufficient facilities and teaching materials, which reduced the efficacy of their lessons.Keyword: Critical literacy, learning process, higher education